Neobjavljeni novac 3. i 4. stoljeća iz numizmatičke zbirke Franjevačkog samostana u Tomislavgradu (Archaeologia Adriatica, 2018)
The paper publishes the 52 specimens of the Roman Imperial coins from the coin collection of the Franciscan Museum in Tomislavgrad (Bosnia and Herzegovina). The oldest among them were dated back to the reign of Emperor Gordian in the first half of the 3rd century (238-244 AD), while the newest ones can be dated to the period of the joint reign of Valentinian I, Valens and Gratian, and to Emperor Valens’ reign, respectively. However, most of the coins belong to the bronze issues of Constantine and his sons, particularly to the series struck during the sole reigns of Constantius II and Constans. With the exception of the dupondius of Gordian III, struck in Viminacium, the specimens published here are the standard coins that circulated in the Roman province of Dalmatia in the 3rd and 4th centuries AD.